Factors that Limit International Competitiveness of European Universities (Economic and Political Thought, 2012)
The article presents the analysis of factors limiting the internationalcompetitiveness of the European universities. It calls for many reformsthat should be implemented by the European universities and decisionmakers,especially in Poland. The author emphasizes that the countries witheconomies based on technological forms, which have effective mechanisms ofknowledge, technology and innovation transfer between business and sciencesectors, will have best prospects in the new global economic reality. This iswhere, i.e. the sector of scientific research and higher education, Polish elitesshould look for new, effective mechanisms of development and strengthenthem just now as any changes in the sector of higher education and researchrequire relatively long time (at least 4 years) to produce results.